2021
DOI: 10.1002/adfm.202100469
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Quantum Metamaterials from High Pressure Melt Infiltration of Metals into Block Copolymer Double Gyroid Derived Ceramic Templates

Abstract: Mesoscale order can lead to emergent properties including phononic bandgaps or topologically protected states. Block copolymers offer a route to mesoscale periodic architectures, but their use as structure directing agents for metallic materials has not been fully realized. A versatile approach to mesostructured metals via bulk block copolymer self‐assembly derived ceramic templates, is demonstrated. Molten indium is infiltrated into mesoporous, double gyroidal silicon nitride templates under high pressure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 56 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…These ideas comprise DNA sections as templates [ 117 ], molecular templates [ 118 ], and biomimetic templates from chitosan [ 119 ]. Other proposals made include self-assembled Si templates [ 120 ], combinations of porous Si with high-resolution electron beam lithography [ 121 ], block copolymer double gyroid-derived ceramic templates [ 122 ], and zeolite [ 123 ]. Using these new approaches, new superconducting materials were also obtained in nanowire form, including MgB and 3-MoN [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…These ideas comprise DNA sections as templates [ 117 ], molecular templates [ 118 ], and biomimetic templates from chitosan [ 119 ]. Other proposals made include self-assembled Si templates [ 120 ], combinations of porous Si with high-resolution electron beam lithography [ 121 ], block copolymer double gyroid-derived ceramic templates [ 122 ], and zeolite [ 123 ]. Using these new approaches, new superconducting materials were also obtained in nanowire form, including MgB and 3-MoN [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…35 The morphologies of block copolymers depend on the thermal equilibrium condition with respect to the volume fraction of monomer blocks. Thus, various morphologies, such as lamellae and cylinders, and even chiral geometries, like gyroid, 36,37 spiral, 38–40 toroid, 41 and helix, can be obtained by exploiting phase separation and reconstructions of block copolymers. For example (Fig.…”
Section: Part 1 3d Self-assembly For Fabrication Of Chiral Metamaterialsmentioning
confidence: 99%
“…In quantum materials, including superconductors, topological insulators, quantum spin liquids or spin ices, quantum-mechanical effects fundamentally alter macroscopic properties . BCPs have begun making inroads into such areas, demonstrating the convergence of soft matter self-assembly science and hard condensed matter physics, for example, in the form of mesostructured superconductors synthesized through structure direction or templating strategies. These studies have shown how BCP nano/mesostructure definition can lead to emergent quantum metamaterials properties via modification of fundamental, quantum-level material characteristics. For example, when indium metal, a type-I superconductor, was confined to the minority networks of a BCP self-assembly directed double gyroid, the nanoscale confinement and periodic mesostructure led to pinning of magnetic vortices on the order of the double gyroid lattice size, resulting in macroscopic type-II superconductor behavior .…”
Section: Introductionmentioning
confidence: 99%
“…BCPs have begun making inroads into such areas, demonstrating the convergence of soft matter self-assembly science and hard condensed matter physics, for example, in the form of mesostructured superconductors synthesized through structure direction or templating strategies. These studies have shown how BCP nano/mesostructure definition can lead to emergent quantum metamaterials properties via modification of fundamental, quantum-level material characteristics. For example, when indium metal, a type-I superconductor, was confined to the minority networks of a BCP self-assembly directed double gyroid, the nanoscale confinement and periodic mesostructure led to pinning of magnetic vortices on the order of the double gyroid lattice size, resulting in macroscopic type-II superconductor behavior . Furthermore, when superconducting niobium nitride-type materials were structure directed by BCPs into four different mesostructures without substantial variation of the X-ray diffraction-measured atomic lattice parameters they displayed a mesostructure-dependent transition temperature ( T c ), that is, a typical fingerprint of metamaterial behavior .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation